THE ECONOMIC IMPACT OF CLIMATE CHANGE ON AGRICULTURAL PRODUCTION SYSTEMS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This paper examines the economic impact of climate change on agricultural production systems, with a focus on both global and regional contexts. Climate change manifests through rising temperatures, changes in precipitation patterns, increased frequency of extreme weather events, and the spread of pests and diseases. These changes have both direct and indirect impacts on agricultural productivity, food security, farm incomes, and rural livelihoods. The study employs a theoretical framework based on climate-economic models, including Ricardian approaches and Computable General Equilibrium (CGE) models, as well as empirical evidence from recent research. The findings highlight that climate change will have an uneven impact on agricultural systems across regions, with developing countries being more vulnerable due to their limited adaptive capacity. Adaptation strategies such as precision agriculture, crop diversification, technological innovation, and policy support are essential for ensuring long-term sustainability. The paper concludes by emphasizing the need for international cooperation, investments in climate-resilient technologies, and inclusive policy frameworks to mitigate adverse economic consequences while promoting sustainable agricultural growth.